PEOPLE POWER DITINJAU DARI PERSPEKTIF AL-QUR’AN DAN SUNNAH - Sati, Ali (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
The term people power in international history, was first used in 1986 when the overthrow of Ferdinand Marcos from the power of the President of the Philippines, while in Indonesia began during the 1998 reform era which was the initial period of the term people power with a typical and popular model back in 2019 especially when the General Election (Election) for Presidential Candidates and Vice-Presidential Candidates (Presidential and Vice President Candidates) is quite aloofly discussed by experts and the public. For that reason, in this paper, the author tries to examine people power from the perspective of the Qur'an and Sunnah that the author will describe in the discussion below